Impact of Standard Bacterial Vaginosis Treatment on the Genital Microbiota, Immune Milieu, and Ex Vivo Human Immunodeficiency Virus Susceptibility. (12th September 2018) - Joag, Vineet; Obila, Onyango; Gajer, Pawel; Scott, Milcah Carol; Dizzell, Sara; Humphrys, Michael; Shahabi, Kamnoosh; Huibner, Sanja; Shannon, Brett; Tharao, Wangari; Mureithi, Marianne; Oyugi, Julius; et al.
Abstract: Background: Genital immunology is a key determinant of human immunodeficiency virus (HIV) susceptibility. Both factors are modulated by bacterial vaginosis (BV) and, to some extent, by Lactobacillus iners, the genital Lactobacillus spp. that predominates in African, Caribbean, and other Black (ACB) women. We conducted a clinical trial to assess the impact of oral metronidazole treatment on the genital immune parameters of HIV acquisition risks in Kenyan women with BV. Methods: The primary endpoint was ex vivo cervical CD4+ T-cell HIV susceptibility after 1 month; secondary endpoints included genital cytokine/chemokine levels, cervical immune cell populations, and the composition of the cervico-vaginal microbiota by 16S ribosomal RNA gene amplicon sequencing. Results: BV resolved (Nugent score ≤ 3) at 1 month in 20/45 participants, and cervical CD4+ T-cell HIV entry was moderately reduced in all participants, regardless of treatment outcome. Resolution of BV and reduced abundances of BV-associated gram-negative taxa correlated with reduced genital interleukin (IL)-1α/β. However, BV resolution and the concomitant colonization by Lactobacillus iners substantially increased several genital chemokines associated with HIV acquisition, including interferon-γ inducible protein (IP)-10, macrophage inflammatory protein (MIP)-3α, and monokine induced by gamma interferon (MIG). In an independent cohort of ACB women, most of whom were BV-free, vaginal chemokines were again closely linked with L. iners abundance, though not other Lactobacillus spp. Conclusions: BV treatment reduced genital CD4+ T-cell HIV susceptibility and IL-1 levels, but dramatically increased the genital chemokines that may enhance HIV susceptibility; the latter effect was related to the restoration of an Lactobacillus iners –dominated microbiota. Further studies are needed before treatment of asymptomatic BV can be recommended for HIV prevention in ACB communities. Abstract : Bacterial vaginosis increases human immunodeficiency virus (HIV) acquisition risks; however, its treatment paradoxically reduces endocervical CD4 T-cell susceptibility to HIV while increasing Lactobacillus iners abundance, causing a broad and dramatic increase in the genital chemokines linked to HIV acquisition risks.